2019
DOI: 10.3171/2018.7.spine18278
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative neurophysiological monitoring for intradural extramedullary spinal tumors: predictive value and relevance of D-wave amplitude on surgical outcome during a 10-year experience

Abstract: OBJECTIVEThe purpose of this study was to evaluate the technical feasibility, accuracy, and relevance on surgical outcome of D-wave monitoring combined with somatosensory evoked potentials (SSEPs) and motor evoked potentials (MEPs) during resection of intradural extramedullary (IDEM) spinal tumors.METHODSClinical and intraoperative neurophysiological monitoring (IONM) data obtained in 108 consecutive patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 25 publications
(53 reference statements)
7
46
2
1
Order By: Relevance
“…Ghadirpour et al retrospectively analyzed a series of IONM in 108 patients with IDEM tumors and reported that D-waves appeared to have a significantly greater predictive value than m-MEPs and SSEPs alone (0.992 vs. 0.798 vs. 0.653; p = 0.023 and p < 0.001, respectively) (40) According to the results of the study, authors suggested to strongly rely on the use of Dwaves, when monitorable (15,41), since it showed to have a statistically significant higher ability to predict postoperative deficits compared with SSEPs and m-MEPs alone, therefore allowing surgeons to proceed with IDEM tumor resection, especially in cases of SSEP and/or MEP loss. In their series, furthermore, no patients with a monitorable D-wave reported permanent motor deficits after surgery at long-term follow-up (40). The aforementioned recommendations to consider IONM only as a diagnostic adjunct, given by the recent "Guidelines for the use of electrophysiological monitoring for surgery of the human spinal column and spinal cord, " were indeed based essentially on two class II studies, but none of them reported the use of D-wave monitoring (16,42).…”
Section: Discussionmentioning
confidence: 98%
“…Ghadirpour et al retrospectively analyzed a series of IONM in 108 patients with IDEM tumors and reported that D-waves appeared to have a significantly greater predictive value than m-MEPs and SSEPs alone (0.992 vs. 0.798 vs. 0.653; p = 0.023 and p < 0.001, respectively) (40) According to the results of the study, authors suggested to strongly rely on the use of Dwaves, when monitorable (15,41), since it showed to have a statistically significant higher ability to predict postoperative deficits compared with SSEPs and m-MEPs alone, therefore allowing surgeons to proceed with IDEM tumor resection, especially in cases of SSEP and/or MEP loss. In their series, furthermore, no patients with a monitorable D-wave reported permanent motor deficits after surgery at long-term follow-up (40). The aforementioned recommendations to consider IONM only as a diagnostic adjunct, given by the recent "Guidelines for the use of electrophysiological monitoring for surgery of the human spinal column and spinal cord, " were indeed based essentially on two class II studies, but none of them reported the use of D-wave monitoring (16,42).…”
Section: Discussionmentioning
confidence: 98%
“…Treatment of these pathologies is surgical, and in recent years effective results have resulted in tumor surgery from the use of technological innovations. Intraoperative neuromonitorisation (IONM), magnetic resonance (MR) tractography, and ultrasonography (USG) have been used for safe and maximum surgical resection (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Furthermore, surgery under the guidance of Sodium-fluorescein (Na-fluorescein) has earned a place in neurosurgery for tumor resection and tumor volume reduction.…”
Section: Introductionmentioning
confidence: 99%
“…However, TES-MEPs are usually used in SCT removal surgeries where craniotomy is not required. PMD in IMSCT surgery is still the presence/absence criterion [1,12]. The loss of muscle MEPs indicates postoperative motor impairment with a specificity of approximately 90% during IMSCT [13].…”
Section: Motor Evoked Potentialsmentioning
confidence: 99%
“…If hypothermia or hypotension is confirmed, correction of the condition can result in return of the SEP parameters to their baseline values in some cases. Multimodal monitoring with combination of MEPs and D waves has been recommended in SCT surgery for favorable long-term outcomes [1][2][3]. The sensitivity and specificity of the test used to predict postoperative motor deterioration in SCT surgery are known to be lower in SEPs than in MEPs [4][5][6].…”
Section: Introductionmentioning
confidence: 99%